2021
DOI: 10.1101/2021.03.17.21253488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Queuing Model for Ventilator Capacity Management during the COVID-19 Pandemic

Abstract: We present a queue model to inform ventilator capacity management under different COVID-19 pandemic scenarios. Our model was used to support ventilator capacity planning during the first wave of the COVID-19 epidemic in British Columbia (BC), Canada. The core of our framework is an extended Erlang loss model, which incorporates COVID-19 case projections, along with the proportion of cases requiring a ventilator, the delay from symptom onset to ventilation, non-COVID-19 ventilator demand, and ventilation time. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
(173 reference statements)
0
1
0
Order By: Relevance
“…They showed that the patient waiting time in the order of consultation, detection or cure of COVID-19 in case of inequalities within the organization improves globally according to the logarithm rule. Zimmerman et al [14] performed a queueing model to report ventilation capacity management in different COVID-19 epidemic scenarios. The model was used to organize ventilation capacity during the first wave of COVID-19 in British Columbia, Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that the patient waiting time in the order of consultation, detection or cure of COVID-19 in case of inequalities within the organization improves globally according to the logarithm rule. Zimmerman et al [14] performed a queueing model to report ventilation capacity management in different COVID-19 epidemic scenarios. The model was used to organize ventilation capacity during the first wave of COVID-19 in British Columbia, Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We have been developing queue network and discrete event simulation (DES) models of patient flow within the acute care system. Our first project was to develop a generalized Erlang loss queue model for access to mechanical ventilators during the first wave of the pandemic (Zimmerman et al 2021). Case project input for the model was provided twice per week by the British Columbia Centre for Disease Control (BC CDC) and a report on model output was sent to the Ministry of Health to inform planning during the early stages of the pandemic.…”
Section: Questionsmentioning
confidence: 99%